Phenotypic and Genotypic Characteristics of SCN1A Associated Seizure Diseases - Chen, Chunhong; Fang, Fang; Wang, Xu; Lv, Junlan; Wang, Xiaohui; Jin, Hong (Frontiers in Molecular Neuroscience, 2022)
Although SCN1A variants result in a wide range of phenotypes, genotype-phenotype associations are not well established. We aimed to explore the phenotypic characteristics of SCN1A associated seizure diseases and establish genotype-phenotype correlations. We retrospectively analyzed clinical data and results of genetic testing in 41 patients carrying SCN1A variants. Patients were divided into two groups based on their clinical manifestations: the Dravet Syndrome (DS) and non-DS groups. In the DS group, the age of seizure onset was significantly earlier and ranged from 3 to 11 months, with a median age of 6 months, than in the non-DS group, where it ranged from 7 months to 2 years, with a median age of 10 and a half months. In DS group, onset of seizures in 11 patients was febrile, in seven was afebrile, in two was febrile/afebrile and one patient developed fever post seizure. In the non-DS group, onset in all patients was febrile. While in the DS group, three patients had unilateral clonic seizures at onset, and the rest had generalized or secondary generalized seizures at onset, while in the non-DS group, all patients had generalized or secondary generalized seizures without unilateral clonic seizures. The duration of seizure in the DS group was significantly longer and ranged from 2 to 70 min (median, 20 min), than in the non-DS group where it ranged from 1 to 30 min (median, 5 min). Thirty-one patients harbored de novo variants, and nine patients had inherited variants. Localization of missense variants in the voltage sensor region (S4) or pore-forming region (S5–S6) was seen in seven of the 11 patients in the DS group and seven of the 17 patients in the non-DS group. The phenotypes of SCN1A-related seizure disease were diverse and spread over a continuous spectrum from mild to severe. The phenotypes demonstrate commonalities and individualistic differences and are not solely determined by variant location or type, but also due to functional changes, genetic modifiers as well as other known and unknown factors.